Combination of dip coating of BMP-2 and spray coating of PLGA on dental implants for osseointegration - Komgrit Eawsakul (2022)
This article describes the design and characterizations of coated implants for stimulating bone regeneration. To achieve successful dental implantation, there are many advances in materials, techniques, and implant design. However, long-term outcomes of osseointegration are considered to be the major factors leading to implant failure. The main potential factors causing early and late implant failures are poor bone quality and bone quantity. In an attempt to increase the success rate of implants, this work coated the surface of implants to increase osteoblast cell attachment. It is known that bone morphogenetic protein-2 (BMP-2) promote osteoblastic cells adhesion. To confirm the osseointegration, the aim of this study was to develop BMP-2 immobilization on titanium (Ti) modified by layer-by-layer technique (LBL). Firstly, the Ti surface was first modified with surface plasma treatment. Secondly, layer-by-layer nanocoating of BMP-2 on dental implant (BMP-2/Ti) and then sprayed with poly(lactide-co-glycolide) (PLGA/BMP-2/Ti). Regarding preparation of modified Ti, Ti was alternatively coated with 15 cycles of BMP-2 and sprayed with 10 cycles of PLGA. The number of layers between BMP-2 and PLGA was 15/10, 30/20, 45/30, 60/40,75/50, 90/60, and 105/70. The result of this study showed that the ratio of 75/50, 90/60, and 105/70 was suitable for BMP-2 coating. Entrapment of BMP-2 of 75/50, 90/60, and 105/70 were 6.94 ± 0.55, 7.07 ± 0.53, and 7.12 ± 0.50 μg, respectively. The coating also possessed homogeneity and good biocompatibility. Moreover, all of these coatings promoted osteoblast cell proliferation and had good stability.